Treatment of Uremic Anemia with Recombinant Erythropoietin also Reduces the Defects in Platelet Adhesion and Aggregation Caused by Uremic Plasma - Zwaginga, Jaap J; IJsseldijk, Martin J W; de Groot, Philip G; Kooistra, Menno; Vos, Jaap; van Es, A; Koomans, Hein A; Struyvenberg, A; Sixma, Jan J (Thrombosis and Haemostasis, 1991)
In the present study, uremic patients on chronic maintenance hemodialysis were treated with recombinant erythropoietin. Before and after 20 weeks of treatment, platelet adhesion and aggregation were studied with perfusions over a sprayed collagen surface and over matrix of cultured endothelial cells with high tissue factor activity. The influence of the erythropoietin induced raise in hematocrit on platelet transport and adhesion was excluded by performing the perfusions at a standard red blood cell concentration. The present study clearly demonstrates that erythropoietin treatment improves platelet adhesion and aggregation in addition to and independent of its effect on the hematocrit.Studies with control platelets resuspended in plasma of untreated patients showed that a uremic plasma factor reduced adhesion and thrombin- and collagen-dependent aggregation. Patient platelets resuspended in control plasma showed no defects. After erythropoietin treatment, the plasma-induced inhibition of adhesion and aggregation had almost completely disappeared from patient plasma.The beneficial effect of the erythropoietin treatment on uremic hemostasis is therefore twofold. The increase of the red blood cell mass improves transport of platelets, and thus adhesion to the vessel wall. The intrinsic defect due to the presence of an inhibitory toxin in uremic plasma is, in large part, corrected. Improved neutralization of uremic toxins by red blood cells or less production of toxins by better oxygenated tissue might play a role in the observed phenomena.